GROWTH IMPROVEMENT OF Rhizophora mucronata Lamk WITH LATERAL ROOT MANIPULATION TECHNIQUE (LRM) IN MUARA ANGKE, NORTH JAKARTA - Cecep Kusmana; Ageng Nurtya; Yadi Setiadi (Jurnal Silvikultur Tropika, 2016)
Mangrove has a strategic functions as a primer producer that able to support the stability between aquatic and terrestrial ecosystems. The damage mangrove plants needs an intense handling to avoid the destruction of mangrove ecosystem. It requires an environmental modification to increase growth quality of mangrove, one of various techniques that can be applied is lateral root manipulation (LRM). This study was aimed to examine the growth response of Rhizophora mucronata seedlings toward the frequency of fertilization by terabuster polymer fertilizer, and addition by rock phosphate and HSC (humate substance complex) fertilizer. Our treatments on this study were different frequency of flushing by 0.5% terabuster polymer fertilizer combined with addition of 500 g rock phosphate, and 0.2% HSC, by using two factorial experiment design on randomized complete block design. The application of LRM combined by addition of rock phosphate and HSC which is flushed by terabuster polymer give a significant effect to the height and stem diameter seedlings. The result of interaction between the treatment fertilization addition and flushing frequency shows that RHF1 (mixed rock phosphate and HSC with flushed by terabuster in a frequency one time in a week) give a significant effect to the stem diameter of seedlings with average growth as large as 0.61 cm (about 254.02% compared to control).Key words: heigth growth, humat substance complex, lateral root manipulation, Rhizophora mucronata Lamk., rock phosphate, stem diameter growth, terabuster.